DERADIKALISASI AGAMA DALAM PEMAHAMAN TEKS-TEKS LITERATUR PENDIDIKAN PESANTREN - Ibrahim, Rustam (Kopertais Wilayah X Jawa Tengah, 2015)
The author’s interest in researching on de-radicalization of religion in the literature of islamic boarding school education was driven by the fact that religion de-radicalization are now starting to touch many aspects of society. Religious radicalism is often associated with terrorism, such as suicide bombers under the pretext of jihad (martyrdom), violence in the name of amar ma'ruf-nahy munkar (commanding the good and forbidding the evil), even now starting to organize religious radicalism in the establishment of the state. Ironically, some of the perpetrators of terrorism are graduates of boarding schools. This is due to the fact that there are several texts in the literature of boarding school education that are vulnerable to radical behaviors, such as jihad, commanding the good, or fighting against non-Muslims. It makes boarding schools are negatively affected despite the fact that they are institutions of Islamic education in Indonesia who spread the teachings of Islam which is rahmatan lil Alamin (blessing for the universe), tolerant, and contextual. Therefore, this study wanted to know about de-radicalization of religion in the understanding of texts in the literature of boarding school education, particularly related to the meaning of jihad, commanding the good, and Islam as the blessing for the universe.This research uses library research, which is a pure literature research. This method is used for obtaining data on de-radicalization in the view of boarding schools using descriptive approach. This research is a study on religious teachings in relation to society, nature, character, and the influence of the thoughts and ideas in forming the character of a group.De-radicalization of religion in the literature of boarding schools includes several things. First, boarding schools should not teach jihad with war, but with education. Next, the applications of amar ma'ruf-nahy munkar must be done through certain stages, so that the direction fits the condition of the object of the missionary endeavor. Violence must not be used as long as it is still possible to use subtle ways since violence is only legalized when the situation is extremely urgent.Keywords: De-radicalisation of Religion, Text, Literature, Boarding School